Optical linearities in semiconductors - Meier, Torsten; Koch, S.W. (Photonic Systems and Applications in Defense and Manufacturing)
A microscope many-body theory for the nonlinear optical response of semiconductors is reviewed. The importance of Coulomb interaction induced carrier correlations is demonstrated in excitonic pump-probe spectra. The influence of excitonic and biexcitonic contributions to coherent pump- induced absorption changes at the exciton frequency are discussed. Absorption changes induced by incoherent exciton and unbound electron-hole populations are studied.